Hydro-chemical Survey of Groundwater of Delhi, India - Masood Alam; Sumbul Rais; Mohd Aslam (E-Journal of Chemistry)
The physicochemical parameters and trace metal contents of water samples from Delhi were assessed. A total of 20 water samples were collected from boring, tube well and hand pump and analyzed for the various physicochemical parameters like pH, conductivity, total dissolved solid, total alkalinity, Ca2+ and Mg2+ hardness, chloride ion, dissolved oxygen, biochemical oxygen demand, sulphate and heavy metal contents like Cu, Cr, Cd, Co, Zn and Ni. The results were compared with BIS standards for drinking water. The quality of water samples under study were within the maximum permissible limits. Therefore, the groundwater samples are fit for human consumption without prior treatment.